The Impact of Social Media Marketing on Electric Vehicle Purchase Intention in Henan: An SOR Perspective - Li, Jing; Gerdruang, Atiporn (Rajapark Journal, 2025)
This study investigates the impact of social media marketing (SMM) on private electric vehicle (PEV)purchase intentions in Henan Province, China, utilizing the Stimulus-Organism-Response (SOR) model as the theoretical foundation. The research objectives were to: (1) examine the direct effect of SMM on purchase intention; (2) assess the mediating role of perceived value; and (3) evaluate the moderating effect of government policies. A quantitative methodology was employed, using a structured questionnaire distributed to 426 private PEV owners in Henan, selected via snowball sampling. Data analysis involved reliability tests, correlation analysis, regression analysis, and mediation/moderation tests. The results demonstrate that SMM has a significant positive direct impact on purchase intention (β=0.872, p<0.001). Furthermore, perceived value partially mediates this relationship, and government policies positively moderate it (interaction β=0.082, p<0.001). This study enriches the SOR framework by integrating SMM and policy dimensions, offering theoretical contributions to PEV adoption literature and practical insights for marketers and policymakers in emerging regional markets.